2017
DOI: 10.2754/avb201786020141
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of Cu, Zn, Mn, and Se concentrations in the hair of South American camelids

Abstract: The aim of this study was to monitor the content of trace elements in the hair of South American camelids and to evaluate the effect of coat colour, species, age, and sex on their concentration in the hair. The samples were collected from 77 animals -23 llamas (Llama guanicoe f. gllama) and 54 alpacas (Llama guanicoe f. pacos) during a spring health check. The concentrations of copper (Cu), zinc (Zn), and manganese (Mn) were determined by Flame Atomic Absorption Spectrometry and selenium (Se) by Hydride Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(67 reference statements)
0
5
0
2
Order By: Relevance
“…Kellaway et al, (1978) concluded that Cu levels in hair were a sensitive index of Cu status of body. However Holasova (2017) also reported that the hair copper concentration did not vary with the age sex, and color in American camelidaes. Combs et al, (1982) reported higher Na content in younger cattle.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Kellaway et al, (1978) concluded that Cu levels in hair were a sensitive index of Cu status of body. However Holasova (2017) also reported that the hair copper concentration did not vary with the age sex, and color in American camelidaes. Combs et al, (1982) reported higher Na content in younger cattle.…”
Section: Resultsmentioning
confidence: 90%
“…Sokola et al, (2009) reported 3.4 to 22.9 mg/kg dry matter in sheep wool; Szczegielniak et al, (2014) reported 3.8-20.0 mg/kg dry matter in cow hair. (Holasova 2017) reported that age sex color had significant affect on the hair manganese content. Rashed et al, (2002) reported the Mn content of goat hair was 879 μg/g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations